The effect of low dose pethidine and diazepam for sedation in Cesarean Section under Sub-Arachnoid Block on mothers satisfaction - Saha, Dilip Kumar; Rahman, Mazibar; Sarkar, Paresh Chandra; Banik, Debasish; Hudaak, Quamrul; Begum, Firoza (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: Cesarean Section (CS) is usually performed when a vaginal delivery would put the baby's or mother's life at risk. Regional anesthesia has the advantage over general anesthesia by allowing mother to remain awake during operation. However, some women prefer general anesthesia as they want to be asleep during the operation. Aim of our study was to see the effect of mild sedation on mothers' satisfaction during CS. Materials and methods: A prospective cross sectional study was undertaken in the department of Anesthesiology, Institute of Child and Mother Health from January 2009 to December 2009. Sixty patients of singletone pregnancy with ASA(American Society of Anesthesiology)-I were randomized into two groups I&II of which one group received sedation with low dose pethidine and diazepam and other group did not get any sedation. Results: Data were analyzed between the groups and within the groups using students'‘t' test and Chi-Square test. A p-value of <0.05 was considered as significant. Patient's parameters like heart rate and blood pressure were not statistically significant between groups, but SpO2 fall was statistically significant. Mother's satisfaction is significantly high (76%) in sedation group than non sedation group. Conclusion: By sedation with low dose pethidine and diazepam, mothers' satisfaction was better achieved without affecting the hemo-dynamic stability. Keywords: sedation; cesarean section; sub-arachnoid block; mothers' satisfaction. DOI: 10.3329/bjog.v24i1.6320 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) : 10-13